Prevention and reversal of neuropathic pain by near-infrared photobiomodulation therapy in male and female rats - Chacur, Marucia; Rocha, Igor R Correia; Harland, Michael E.; Green-Fulgham, Suzanne M.; de Almeida, Sonia Regina Yokomizo; Ciena, Adriano Polican [UNESP]; Watkins, Linda R. (Elsevier, 2024)
Pathological nociception arising from peripheral nerve injury impacts quality of life. Current therapeutics are generally ineffective. However, photobiomodulation therapy (PBMT) has shown promise in addressing this issue. We aimed to assess the potential anti-allodynic effects of 2 p.m. protocols, each applied transcutaneously over the peripheral nerve injury. In addition to evaluating nociceptive behavior, we also conducted morphological analysis using electron microscopy (EM) to investigate potential ultrastructural changes at the cellular level. We sought to determine, using the chronic constriction injury (CCI) model, whether our parameters could alleviate established allodynia and/or dampen allodynia development. Adult male and female rats with CCI or sham were treated with PBMT (850-nm wavelength) for 2 min, 3 times a week over three or four weeks across three studies, where PBMT began either before or after CCI. Allodynia was assessed prior to surgery and across weeks and, at the conclusion of the third study, sciatic nerve was processed for EM and histomorphometrically evaluated. The results showed that PBMT before versus after CCI injury yielded similar behaviors, effectively decreasing allodynia. Interestingly, these positive effects of PBMT do not appear to be accounted by protection of the sciatic injury site, based on EM. CCI reliably decreased axon size and the number of myelinated axons present in both PBMT and control groups. While PBMT reduced the number of C-fibers in CCI samples, no improvement in any measure was observed in response to PBMT.
Keywords: Allodynia; Chronic constriction injury; Electron microscopy; Histomorphometric analysis; Sciatic nerve